2014
DOI: 10.1186/2045-8118-11-25
|View full text |Cite
|
Sign up to set email alerts
|

Effect of transporter inhibition on the distribution of cefadroxil in rat brain

Abstract: BackgroundCefadroxil, a cephalosporin antibiotic, is a substrate for several membrane transporters including peptide transporter 2 (PEPT2), organic anion transporters (OATs), multidrug resistance-associated proteins (MRPs), and organic anion transporting polypeptides (OATPs). These transporters are expressed at the blood–brain barrier (BBB), blood-cerebrospinal fluid barrier (BCSFB), and/or brain cells. The effect of these transporters on cefadroxil distribution in brain is unknown, especially in the extracell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 48 publications
1
14
0
1
Order By: Relevance
“…Depending on the tissue studied, it is difficult to influence the probe length. When measuring CSF concentrations in cisterna magna in rats, only a 1-mm probe length is possible (55), while a 3-mm probe length can be used in striatum, and a 10-mm probe length in vena jugularis (56).…”
Section: Flow Rates and Probe Lengthsmentioning
confidence: 99%
“…Depending on the tissue studied, it is difficult to influence the probe length. When measuring CSF concentrations in cisterna magna in rats, only a 1-mm probe length is possible (55), while a 3-mm probe length can be used in striatum, and a 10-mm probe length in vena jugularis (56).…”
Section: Flow Rates and Probe Lengthsmentioning
confidence: 99%
“…Cefadroxil is a substrate of several CNS barrier transporters including the organic anion transporters (OATs) [29], multidrug resistance-associated proteins (MRPs) [30,31], and organic anion transporting polypeptides (OATPs) [32]. Moreover, our previous study showed that co-administration of probenecid (an inhibitor of OATs, MRPs, and OATPs) caused a 2.5-fold increase in the K p,uu of cefadroxil in rat brain ECF during microdialysis [22]. This finding supports our current study results, suggesting that cefadroxil is, indeed, effluxed from brain to plasma by PEPT2 along with the OATs, MRPs and/or OATPs.…”
Section: Discussionmentioning
confidence: 99%
“…At present, cephalosporin antibiotics (e.g., ceftriaxone and cefotaxime) used to treat CNS infections [48] are not PEPT2 substrates [49]. Cefadroxil, as a substrate of multiple efflux transporters including PEPT2, has very low levels in CSF and brain ECF, thereby, excluding its use for CNS infections [22]. Thus, caution should be exercised in developing drug candidates having the general structural features of PEPT2 substrates [3,50] for diseases of the brain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A Margareta Hammarlund-Udenaes vezette svéd kutatócsoport agyi mikrodialízissel vizsgálta mind az agyszöveti ECF, mind pedig az oldalkamrai liquor (CSF) cefadroxilkoncentrációit probenecid -mint OAT, OATP és MRP inhibitor -jelenlétében és hiányában [35] patkányokon. Nagaya és mtsai majmokon végzett kísérlete-ikben hasonlították össze a mikrodializátumokban, illetve a ciszternális liquorban mérhető anyagkoncentrációkat P-gp szubsztrátok esetén [36].…”
Section: Vizsgálati Módszerekunclassified